A Comparative Analysis of Verbs in English and Uzbek Languages (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This paper presents a comprehensive comparative analysis of verbs in English and Uzbek languages, two linguistically distinct yet significant languages. Through an examination of their morphological, syntactic, and semantic features, this study aims to highlight similarities and differences in verb structures, conjugations, tense systems, and aspectual distinctions. Additionally, the research explores the cultural and historical influences shaping the evolution of verbs in both languages, shedding light on how linguistic diversity reflects broader socio-cultural contexts. By employing a contrastive linguistic approach, this analysis contributes to a deeper understanding of linguistic typology and facilitates language learning and translation practices between English and Uzbek.